Web-based Visual Analytics of Lifestyle Data in MyHealthAvatar - Youbing Zhao; Farzad Parvinzamir; Xia Zhao; Zhikun Deng; Feng Dong; Nikolaos Ersotelos; Gordon Clapworthy (EAI Endorsed Transactions on Scalable Information Systems, 2016)
MyHealthAvatar is a project designed to collect lifestyle and health data to promote citizen’s wellbeing. As a lifetime companion of citizens the amount of data to be collected is large. It is almost impossible for citizens, patients and doctors to view, utilise and understand these data without proper visual presentation and user interaction. Visual analytics of lifestyle data is one of the key features of MyHealthAvatar. This paper presents the visual analytics components in MyHealthAvatar to facilitate health and lifestyle data presentation and analysis, including 3d avatar, dashboard, diary, timeline, clock view and map. These components can be used cooperatively to achieve flexible visual analysis of spatial temporal lifestyle and health data.